'A holistic approach': incorporating sustainability into biopedagogies of healthy eating in Sweden's dietary guidelines. Issue 8 (10th September 2020) - Bergman, Karolin; Lövestam, Elin; Nowicka, Paulina; Eli, Karin
Abstract: Dietary guidelines can be considered a pedagogical tool, designed to promote healthy eating at the population level. In this study, we critically examine the biopedagogies implicated in Sweden's official dietary guidelines. Published in 2015, these guidelines take a potentially innovative 'holistic approach' to food and eating, addressing the challenge of formulating dietary advice that considers both human health and environmental concerns. Applying Bacchi´s 'What's the problem represented to be?' approach, we interrogate how the guidelines frame the interplay of public health concerns and environmental concerns in making food choices. We find that the biopedagogies of sustainable eating, as presented in these guidelines, implicate the subject position of the ideal eater . The ideal eater values sustainability, has high cultural capital, and draws on both taste and nutritional knowledge to make good food choices. However, while the ideal eater is expected to be aware of environmental issues, these are incorporated into the ideal eater's choices only in addition to the primary concern of health. Thus, although the guidelines frame a 'holistic approach' as the solution to both health and environmental concerns, in cases where health and environmental priorities conflict, the guidelines' biopedagogies of sustainable eating align with earlier biopedagogies of healthy eating.